Social Robotics 8th International Conference, ICSR 2016, Kansas City, MO, USA, November 1-3, 2016 Proceedings - Agah, Arvin; Cabibihan, John-John.; Howard, Ayanna M.; Salichs, Miguel A.; He, Hongsheng (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book constitutes the refereed proceedings of the 8th International Conference on Social Robotics, ICSR 2016, held in Kansas City, MO, USA, in November 2016. The 98 revised full papers presented were carefully reviewed and selected from 107 submissions. The theme of the 2016 conference is Sociorobotics: Design and implementation of social behaviors of robots interacting with each other and humans. In addition to technical sessions, ICSR 2016 included three workshops: The Synthetic Method in Social Robotics (SMSR 2016), Social Robots: A Tool to Advance Interventions for Autism, and Using Social Robots to Improve the Quality of Life in the Elderly. .
Learning robot navigation behaviors by demonstration using a RRT* planner -- Adaptive Robot Assisted Therapy using Interactive Reinforcement Learning -- Personalization Framework for Adaptive Robotic Feeding Assistance -- A Framework for Modelling Local Human-Robot Interactions based on unsupervised learning -- Using Games to Learn Games: Game Theory Representations as a source for Guided Social Learning -- User Evaluation of an Interactive Learning Framework for Single-Arm and Dual-Arm Robots -- Formalizing Normative Robot Behavior -- Decision-Theoretic Human-Robot Interaction: Designing Reasonable and Rational Robot Behavior -- Physiologically Inspired Blinking Behavior for a Humanoid Robot -- Infinite personality space for non-fungible robots -- Investigating the Differences in Effects of the Persuasive Message's Timing During Science Learning to Overcome the Cognitive Dissonance -- Investigating the Effects of the Persuasive Source's Social Agency Level and the Student's Profile to Overcome the Cognitive Dissonance -- Responsive Social Agents; Feedback-sensitive behavior generation for social interactions -- A Human-Robot Competition: Towards Evaluating Robots' Reasoning Abilities for HRI -- The Effects of Cognitive Biases in Long-term Human-Robot Interactions: Case Studies using three Cognitive Biases on MARC the Humanoid Robot -- Ethical Decision Making in Robots: Autonomy, Trust and Responsibility -- How Facial Expressions and Small Talk May Influence Trust in a Robot -- A Study on Trust in a Robotic Suitcase -- How Much Should a Robot Trust the User Feedback? Analyzing the Impact of Verbal Answers in Active Learning -- Recommender Interfaces: the More Human-like, the More Humans Like -- Designing a Social Robot to Assist in Medication Sorting -- Other-oriented Robot Deception: How can a robot's deceptive feedback help humans in HRI? -- Ethically-Guided Emotional Responses for Social Robots : Should I be Angry? -- Interactive Navigation of Mobile Robots Based on Human‘s Emotion -- Social Human-Robot Interaction: a new Cognitive and Affective Interaction-Oriented Architecture -- MuDERI: Multimodal Database for Emotion Recognition among Intellectually Disabled Individuals -- “How is his/her mood”: A Question that a Companion Robot may be able to answer -- Emotion in Robots Using Convolutional Neural Networks -- Rhythmic Timing in Playful Human-Robot Social Motor Coordination -- The effects of an impolite vs. a polite robot playing rock-paper-scissors -- Qualitative User Reactions to a Hand-Clapping Humanoid Robot -- Nonlinear Controller of Arachnid Mechanism Based on Theo Jansen -- Designing and Assessing Expressive Open-Source Faces for the Baxter Robot -- Spontaneous Human-Robot Emotional Interaction through Facial Expressions -- Functional and Non-Functional Expressive Dimensions: Classification of the Expressiveness of Humanoid Robots -- Facing Emotional Reactions Towards a Robot – An Experimental Study Using FACS -- Head and Face Design for a new Humanoid Service Robot -- The Influence of Robot Appearance and Interactive Ability in HRI: A Cross-Cultural Study -- Congruency matters - How ambiguous gender cues increase a robot's uncanniness -- Collaborative Visual Object Tracking via Hierarchical Structure -- Data Augmentation for Object Recognition of Dynamic Learning Robot -- Rotational Coordinate Transformation for Visual-Inertial Sensor Fusion -- Developing an Interactive Gaze Algorithm for Android Robots -- Recovery Behavior of Artificial Skin Materials after Object Contact -- One-shot evaluation of the control interface of a robotic arm by non-experts -- A Novel Parallel Pinching and Self-adaptive Grasping Robotic Hand -- PCSS Hand: An Underactuated Robotic Hand with a Novel Parallel-Coupled Switchable Self-adaptive Grasp -- JLST Hand: A Novel Powerful Self-Adaptive Underactuated Hand with Joint-Locking and Spring-Tendon Mechanisms -- Path Analysis for the Halo Effect of Touch Sensations of Robots on Their Personality Impressions -- A Human-robot speech interface for an autonomous marine teammate -- Annotation of Utterances for Conversational Nonverbal Behaviors -- Identifying Engagement from Joint Kinematics Data for Robot Therapy Prompt Interventions for Children with Autism Spectrum Disorder -- Social Robots and Teaching Music to Autistic Children: Myth or Reality? -- Development of an ABA Autism Intervention Delivered by a Humanoid Robot -- Interactive Therapy Approach through Collaborative Physical Play between a Socially Assistive Humanoid Robot and Children with Autism Spectrum Disorder -- Examine the Potential of Robots to Teach Autistic Children Emotional Concepts: A Preliminary Study -- Longitudinal Impact of Autonomous Robot-mediated Joint Attention Intervention for Young Children with ASD -- Culture as a Driver for the Design of Social Robots for Autism Spectrum Disorder Interventions in the Middle East -- Robo2Box: A Toolkit to Elicit Children's Design Requirements for Classroom Robots -- Interaction with Artificial Companions: Presentation of an Exploratory Study -- Design and Development of Dew: An Emotional Social-Interactive Robot -- RASA: A Low-Cost Upper-Torso Social Robot Acting as a Sign Language Teaching Assistant -- Robust Children Behavior Tracking for Childcare Assisting Robot By Using Multiple Kinect Sensors -- Learning with or from the Robot: Exploring Robot Roles in Educational Context with Children -- Automatic Adaptation of Online Language Lessons for Robot Tutoring -- Robots in the Classroom: What Teachers Think about Teaching and Learning with Education Robots -- The Inﬂuence of a Social Robot’s Persona on how it is Perceived and Accepted by Elderly Users -- From Social Practices to Social Robots - User-Driven Robot Development in Elder Care -- Co-design and robots: a case study of a robot dog for aging people -- An Effort to Develop a Web-Based approach to Assess the Need for Robots Among the Elderly -- Predicting the intention of human activities for real-time human-robot interaction (HRI) -- The ENRICHME Project: Lessons Learnt from a First Interaction with the Elderly -- Design and Implementation of a Task-oriented Robot for Power Substation -- The MuMMER project: Engaging human-robot interaction in real-world public spaces -- Introducing IOmi - A Female Robot Hostess for Guidance in a University Environment -- Colleague or Tool?: Interactivity Increases Positive Perceptions of and Willingness to Interact With a Robotic Co-Worker -- Help Me! Sharing of Instructions Between Remote and Heterogeneous Robots -- Enabling Symbiotic Autonomy in Short-Term Interactions: a User Study -- Conceptual framework for RoboDoc: A New Social Robot for Research Assistantship -- Mechanical design of Christine, the friendly social robot for the service industry -- Influence of user’s personality on task execution when reminded by a robot -- Comparing Ways to Trigger Migration between a Robot and a Virtually Embodied Character -- Does the Safety Demand Characteristic Influence Human-Robot Interaction? -- On Designing Socially Acceptable Reward Shaping -- Motivational Effects of Acknowledging Feedback from a Socially Assistive Robot -- Who am I? What are You? Identity Construction in Encounters between a Teleoperated Robot and People with Acquired Brain Injury -- Contribution towards Evaluating the Practicability of Socially Assistive Robots - by Example of a Mobile Walking Coach Robot -- Philosophy of Social Robotics: Abundance Economics -- Toward a Hybrid Society: The transformation of robots, from objects to social agents -- Iterative Design of a System for Programming Socially Interactive Service Robots -- Engagement Detection During Deictic References In Human Robot Interaction -- Making Turn-taking Decisions for an Active Listening Robot for Memory Training -- Look at me now: Investigating delayed disengagement for ambiguous human-robot stimuli -- Concurrency Simulation in Soccer -- Let the User Decide! User Preferences regarding Functions, Apps, and Interfaces of a Smart Home and a Service Robot -- Welcome to the Future – How Naïve Users Intuitively Address an intelligent Robotics Apartment -- Better than Human: About the Psychological Superpowers of Robots -- A Method for Establishing Correspondences between Hand-Drawn and Sensor-Generated Maps.
SpringerLink eBooks.
Keywords: Computer science; Computer communication systems; User interfaces (Computer systems).; Artificial intelligence; Computers and civilization; Robotics; Automation; Computer Science; Artificial Intelligence (incl. Robotics).; Computers and Society; User Interfaces and Human Computer Interaction; Robotics and Automation; Information Systems Applications (incl. Internet).; Computer Communication Networks